Bilingual Academic Competition on Region Studies as an Effective Agent of Giving a Boost to Gifted School Children - Ryzhova, Tatiana Semyonovna; Kuznetsova, Natalia Yurevna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
This article's focus is universities helping young learners make a motivated choice of their personal learning path. The necessity to support students' motivation from their early years to adulthood is emphasized. The article also introduces a notion of “bilingual academic competition”, which is regarded as one of the most efficient ways to achieve the goal, providing for the development of students’ creative skills, professional potential, and helping to recognize the learners identified as the gifted.